Geophysical survey at Talos Dome, East Antarctica: The search for a new deep-drilling site - Frezzotti, M; Bitelli, G; De Michelis, B; Deponti, A; Forieri, A; Gandolfi, S; Mancini, F; Remy, F; Tabacco, I; Urbini, S; Vittuari, L; Zirizzotti, L.; et al. (Annals of Glaciology, 2004)
Talos Dome is an ice dome on the edge of the East Antarctic plateau; because accumulation is higher here than in other domes of East Antarctica, the ice preserves a good geochemical and palaeoclimatic record. A new map of the Talos Dome area locates the dome summit using the global positioning system (GPS) (72°47′14′′S, 159°04′2′′E; 2318.5 m elevation (WGS84)). A surface strain network of nine stakes was measured using GPS. Data indicate that the stake closest to the summit moves south-southeast at a few cm a-1. The other stakes, located 8 km away, move up to 0.33 m a-1. Airborne radar measurements indicate that the bedrock at the Talos Dome summit is about 400 m in elevation, and that it is covered by about 1900 m of ice. Snow radar and GPS surveys show that internal layering is continuous and horizontal in the summit area (15 km radius). The depth distribution analysis of snow radar layers reveals that accumulation decreases downwind of the dome (north-northeast) and increases upwind (south-southwest). The palaeomorphology of the dome has changed during the past 500 years, probably due to variation in spatial distribution of snow accumulation, driven by wind sublimation. In order to calculate a preliminary age vs depth profile for Talos Dome, a simple one-dimensional steady-state model was formulated. This model predicts that the ice 100 m above the bedrock may cover one glacial-interglacial period.